Improving users' consistency when recalling location sharing preferences - Venkatanathan, Jayant; Ferreira, Denzil; Benisch, Michael; Lin, Jialiu; Karapanos, Evangelos; Kostakos, Vassilis; Sadeh, Norman; Toch, Eran (My University, 2011)
This paper presents a study of the effect of one instance of contextual cues, trajectory reminders, on the recollection of location sharing preferences elicited using a retrospective protocol. Trajectory reminders are user interface elements that indicate for a particular location of a person's trail across a city the locations visited before and after. The results of the study show that reminding users where they have been before and after a specific visited location can elicit more consistent responses in terms of stated location sharing preferences for that location visit. This paper argues that trajectory reminders are useful when collecting preference data with retrospective protocols because they can improve the quality of the collected data.
Keywords: Location sharing preferences; Consistency; Retrospective protocols